DETERMINAN STATUS MISKIN RUMAH TANGGA DI KABUPATEN LEMBATA TAHUN 2024 - Yulianus Ronaldias (Jurnal Statistika Terapan (ISSN 2807-6214), 2025)
Lembata Regency is one of the regions with a high poverty rate in East Nusa Tenggara Province. As of March 2024, the poverty rate in Lembata Regency reached 24.22 percent, which remains far above both the provincial and national averages. Research on poverty in Lembata Regency is still very limited, even though evidence-based policy is crucial to improving policy effectiveness. This study aims to analyze the characteristics and determinants of household poverty status in Lembata Regency. The analysis uses raw data from the March 2024 National Socio-Economic Survey (Susenas) conducted by Statistics Indonesia (BPS). The analytical method applied is binary logistic regression. The results show that residential area, age of household head, number of household members, main employment sector of the household head, and household asset ownership are statistically significant in influencing household poverty status in Lembata Regency. Based on these findings, the government should improve the quality of rural infrastructure to enhance public access to basic services. In addition, comprehensive policy interventions in the agricultural sector are needed, including agricultural land expansion, price stabilization, ensuring market access, and farmer empowerment.